Elective module in undergraduate medical curriculum: Implementation and its perception - Padmanabh Inamdar; Dhanashree P. Inamdar; Anuradha B.; Malatesh Undi (Universitas Pendidikan Indonesia, 2025)
The National Medical Commission (NMC) in India introduced the elective module proactively. There is a need to study the ease and difficulty of implementation along with student and faculty perceptions to initiate corrective action. Hence, the present study was undertaken to explore the perception of faculty and students towards elective modules and understand the ease and difficulty of implementing Elective modules. A cross-sectional study was conducted after the implementation of the elective module, and student and faculty responses were collected using a Google Doc questionnaire. Responses were collected in the form of a 5-point Likert scale. A total of 120 responses from medical students and 40 responses from faculty were included for data analysis. Most students felt that the elective module met their expectations, and the staff was supportive. Knowledge and experience gained were satisfactory, which led to overall professional development. Faculty were also satisfied and needed to include it in the medical curriculum. However, few believed it led to additional work burden. It also requires strengthening infrastructure facilities, faculty availability, interdepartmental coordination, and development programs. Implementing the elective module was a satisfactory learning experience for faculty and students. However, there is room for improvement and refinement. Abstrak Modul pilihan diperkenalkan secara proaktif oleh National Medical Commission (NMC) di India. Perlu dikaji kemudahan dan kesulitan pelaksanaan serta persepsi mahasiswa dan dosen agar tindakan perbaikan dapat dimulai. Oleh karena itu penelitian ini dilakukan dengan tujuan untuk mengetahui persepsi dosen dan mahasiswa terhadap modul elektif serta memahami kemudahan dan kesulitan dalam mengimplementasikan modul elektif. Studi cross-sectional dilakukan setelah pelaksanaan modul elektif dan tanggapan mahasiswa dan fakultas dikumpulkan menggunakan kuesioner Google Doc. Tanggapan dikumpulkan dalam bentuk Likert 5 poin. Sebanyak 120 tanggapan dari mahasiswa kedokteran dan 40 tanggapan dari fakultas dimasukkan untuk analisis data. Sebagian besar siswa merasa bahwa modul pilihan memenuhi harapan mereka, staf mendukung. Pengetahuan dan pengalaman yang diperoleh memuaskan dan mengarah pada pengembangan profesional secara keseluruhan. Fakultas juga merasa puas dan merasa perlu untuk memasukkannya ke dalam kurikulum kedokteran. Namun, hanya sedikit yang percaya bahwa hal ini menyebabkan beban kerja tambahan. Hal ini juga memerlukan penguatan sarana prasarana, ketersediaan fakultas, koordinasi antar departemen, dan program pengembangan fakultas. Penerapan modul pilihan merupakan pengalaman belajar yang memuaskan baik bagi dosen maupun mahasiswa. Namun, masih ada ruang untuk perbaikan dan penyempurnaan. Kata Kunci: fakultas; mahasiswa; modul pilihan; persepsi